Effectiveness of Poster-Based Nutrition Counseling on Mothers’ Knowledge in Krembangan Selatan Health Center - Rizal Wicaksono Agung; Mujayanto; Riezky Faisal Nugroho; Dian Shofiya (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Stunting remains a public health problem in Surabaya, where effective educational interventions are needed to enhance maternal knowledge on balanced nutrition. This study aimed to evaluate the effect of counseling using poster media on balanced nutrition knowledge among mothers of stunted or at-risk toddlers. A quasi-experimental study with a one-group pretest-posttest design was conducted at the Krembangan Selatan Community Health Center, involving 33 mothers selected through non-probability sampling. Primary data were collected through validated questionnaires administered before and after the intervention. The counseling used posters illustrating the balanced nutrition pyramid and the